Antibiotic prophylaxis in open inguinal hernia repair: a literature review and summary of current knowledge - Mateusz T. Zamkowski; Wojciech Makarewicz; Jerzy Ropel; Maciej Bobowicz; Michał Kąkol; Maciej Śmietański (Videosurgery and Other Miniinvasive Techniques)
More than 1 million inguinal hernia repairs are performed in Europe and the US annually. Although antibiotic prophylaxis is not required in clean, elective procedures, the routine use of implants (90% of inguinal hernia repairs are performed with mesh) makes the topic controversial. The European Hernia Society does not recommend routine antibiotic prophylaxis for elective inguinal hernia repairs. However, the latest randomized controlled trial, published by Mazaki et al., indicates that the use of prophylaxis is effective for the prevention of surgical site infection. Unnecessary prophylaxis contributes to the development of bacterial resistance and significantly increases healthcare costs. This review documents clinical trials on inguinal hernia repairs with mesh and summarizes the current knowledge. It also tries to solve certain problems, namely: what constitutes a real risk factor, late-onset infection, and how the “surgical environment” impacts on the need to use antibiotic prophylaxis.